PTU-023 Sedation In The Endoscopy Department – Do We Need More Training?. (9th June 2014) - Mohanaruban, A; Bryce, K; Radhakrishnan, A; Gallaher, J; Trembling, P; Johnson, G
Abstract : Introduction: The 2004 report of the National Confidential Enquiry into Patient Outcome and Death (NCEPOD) highlighted that only 35% of endoscopists surveyed were known to have attended courses on safe sedation. The report recommended that all those responsible for the administration of sedation in the endoscopy department should receive formal training and clear protocols for the administration of sedation should be made available and implemented. Methods: We undertook a paper survey of 40 gastroenterology trainees across 5 UK Deaneries during December 2013 to determine current practices of sedation and training in endoscopy as well as level of knowledge of the sedation agents. Results: All 40 of the trainees surveyed responded. 21 (53%) had received formal training in sedation for endoscopy with the most common setting for training being at local trust induction. 35 (88%) would value an introductory course in sedation as part of local trust induction. Only 14 (35%) were aware of a sedation protocol in their department. 27 (68%) reported Fentanyl as the commonest first-line opioid used, although it was rarely administered in upper GI endoscopy. 28 (70%) trainees performed the majority of their upper GI endoscopies 'unsedated' with throat-spray only. These findings were similar in both sedation-trained and non-trained cohorts. For colonoscopy, 18 (90%) of those who had received formal training in sedation would administer an opioid first, before Midazolam, whereas 13 (72%) trainees without sedation training would use this sequence. 28 (70%) trainees stated correctly the maximum doses for Midazolam and Fentanyl as recommended by BSG guidelines, and were appropriately cautious about the initial dose of Midazolam administered to an elderly patient. 14(74%) of the trained cohort correctly said that Fentanyl takes 1–2 min to act, compared to 7 (39%) in the untrained cohort. All trainees surveyed knew the reversal agents for Midazolam and Fentanyl. Conclusion: 47% of trainees did not receive structured training in safe sedation, despite national guidelines advising this to be an essential part of the training program. The majority of trainees would value sedation training. We also identified some gaps in trainees' knowledge of the action of sedation agents. We propose that a formal training session in sedation or an e-learning module could be incorporated as part of a deanery or trust induction for gastroenterology and regularly reviewed thereafter. References: NCEPOD 2004: Scoping our practice BSG 2003: Guidelines on safety and sedation during endoscopic procedures Disclosure of Interest: None Declared.